A Literature Study on Usage of and Satisfaction Levels with Combined Treatment Including Oriental and Western Medicine - Lim Jung-Hun; Lim Sung-Min (Korean Pharmacopuncture Institute, 2012)
Objective: This study aimed to summarize and analyze the usage of and the satisfaction levels with combined treatment including Oriental and Western medicine. Methods: We searched studies on the usage of and the satisfaction levels with combined treatment including Oriental and Western medicine over the past 10 yrs (2001-2011) from 3 Korean databases (National Assembly Library, Research Information Service System, and National Discovery for Science Leaders). The reviewers also conducted a summarizing analysis by sampling the literature according to the type of study, study period, region, study subjects, sample size, type of sampling, research method, data analysis, study instruments, main results, etc. Results: When the main results of six studies on combined treatment usage and satisfaction levels were considered together, the most important decisive factor in determining the usage of combined treatment was the illness of the patient, followed by the patient's occupation, sex, age, education, marital status, religion, treatment cost, and treatment results. In addition, the most important factor that determined satisfaction levels with combined treatment was age, followed by education, religion, income, health status, treatment procedures, staff attitude, and cleanliness. Conclusions: Elderly patients with musculoskeletal, cerebro-vascular, and circulatory system illnesses are more likely to prefer combined treatment over independent Oriental or Western treatment and are more likely to request specialized, adjusted medical care.